- 4(1/2)x - (3/7) = (1/4)
- 4(1/2)x = (1/4) + (3/7)
- (9/2)x = (7+12)/28
-(9/2)x = 19/28
x = (19/28) * 2 / 9
x = (19/14) / 9
x = 19 / (14*9)
x = 19 / 126
2x^3y+18xy-10x^2y-90y
= 2xy(x^2 + 9)- 10y(x^2 + 9)
= (x^2 + 9)(2xy - 10y)
= (x^2 + 9) 2y(x - 5)
= 2y (x^2 + 9) (x - 5)
240,000 = 24 x 10,000 but 10,000 = 10 x 10 x 10 x 10 = 10⁴, then:
240,000 = 24 x 10⁴
Answer:
x = 4 ±√26
Step-by-step explanation:
Please write this as x^2 - 8x = 10, or x^2 - 8x - 10 = 0. " ^ " indicates exponentiation.
Let's complete the square:
x^2 - 8 x can be rewritten as
x^2 - 8x + 16 - 16, and so
x^2 - 8x = 10 becomes x^2 - 8x + 16 - 16 - 10 = 0, or
(x - 4)^2 = 26
Taking the square root of both sides, we get:
x - 4 = ±√26, or
x = 4 ±√26